2005
DOI: 10.1093/annonc/mdi923
|View full text |Cite
|
Sign up to set email alerts
|

Home therapy for deep vein thrombosis and pulmonary embolism in cancer patients

Abstract: Outpatient treatment of deep vein thrombosis (DVT) has become a common practice in uncomplicated patients. Few data are still present in patients with comorbidity (such as cancer) or concomitant symptomatic pulmonary embolism. Cancer patients with DVT are often excluded from home treatment because they have a higher risk of both bleeding and recurrent DVT. We tested the feasibility and safety of the Home Treatment (HT) program for acute DVT a PE in cancer patients. Patients were treated as outpatients unless t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 13 publications
3
74
0
2
Order By: Relevance
“…The remaining 11 studies were included in our systematic review. Eight were prospective cohort studies [8,[11][12][13][31][32][33][34]] and 3 were randomized controlled trials (RCT's) [16,17,35]. Furthermore, 2 studies did not report outcomes at 3 months and could not be used in our pooled meta-analysis [12,13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 11 studies were included in our systematic review. Eight were prospective cohort studies [8,[11][12][13][31][32][33][34]] and 3 were randomized controlled trials (RCT's) [16,17,35]. Furthermore, 2 studies did not report outcomes at 3 months and could not be used in our pooled meta-analysis [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that outpatient management or early discharge of patients with acute PE is safe and effective [8][9][10][11][12][13]. Two systematic reviews suggested that patients with acute PE treated as outpatients had low incidences of major bleeding, recurrent venous thromboembolism (VTE), and mortality [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…No RCTs were identified. Seven observational studies had a prospective cohort design [19,20,22,27,31,35,37]. No study fulfilled the criteria required for high quality (table 1).…”
Section: Resultsmentioning
confidence: 99%
“…No study fulfilled the criteria required for high quality (table 1). A single study, which only enrolled patients with cancer, was of medium quality [35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation